2015
DOI: 10.1063/1.4932339
|View full text |Cite
|
Sign up to set email alerts
|

Localized electron heating by strong guide-field magnetic reconnection

Abstract: Localized electron heating of magnetic reconnection was studied under strong guide-field using two merging spherical tokamak plasmas in the University of Tokyo Spherical Tokamak experiment. Our new slide-type two-dimensional Thomson scattering system is documented for the first time the electron heating localized around the X-point. Shape of the high electron temperature area does not agree with that of energy dissipation term Et·jt. If we include a guide-field effect term Bt/(Bp+αBt) for Et·jt, the energy dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…been quantitatively evaluated, electron heating (or energization) near the X-point in collisionless reconnection is not yet well understood. Similar local electron heating has also been observed in UTST experiments [11], and it was concluded that the thermalization of energetic electrons accelerated by a reconnection electric field along a guide (toroidal) magnetic field perpendicular to a reconnection (poloidal) magnetic field can account for local electron heating.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…been quantitatively evaluated, electron heating (or energization) near the X-point in collisionless reconnection is not yet well understood. Similar local electron heating has also been observed in UTST experiments [11], and it was concluded that the thermalization of energetic electrons accelerated by a reconnection electric field along a guide (toroidal) magnetic field perpendicular to a reconnection (poloidal) magnetic field can account for local electron heating.…”
Section: Introductionsupporting
confidence: 73%
“…There are two possible origins of the SXR bursts: thermal and non-thermal electrons generated during reconnection. The Thomson scattering measurement revealed that the electron temperature in the UTST merging experiment was up to 30 eV [11], which is much lower than the absorption edge of the filter used in the present study, as shown in Fig. 3.…”
Section: Methodsmentioning
confidence: 51%
“…Figure 4 shows 2D electron temperature and density profiles during discharges 21374-21380 (P6 coils are used to shift the vertical position of Thomson scattering measurement 50 ) after the fast reconnection event (1:2 m < r sep < 1:3 m for the vertical scan shots at t ¼ 8; 9; 10; 11; 12 ms). The electron temperature profile forms a characteristic peaked structure around the X-point where localized electron acceleration and heating by the parallel electric field are reported in the high guide field laboratory merging (driven reconnection) experiment in UTST (University of Tokyo Spherical Tokamak), [59][60][61] while the electron density increases downstream. In contrast to the no guide field experiment in MRX 27,28 where electron energy gain is quickly transported downstream, the higher toroidal field in MAST strongly…”
Section: -2mentioning
confidence: 91%
“…Negligible emission was observed in the latter merging phase of t > 60 µs while the reconnection electric field was still kept high. Previous Thomson scattering measurements in the UTST merging experiment had shown that the electron temperature during the merging start-up increased up to 25 eV in the vicinity of the X point [16]. The measured electron temperature indicates that the bulk electron heating was not large enough to account for the SXR burst observed in the middle merging phase.…”
Section: Methodsmentioning
confidence: 79%